Health Education about Healthy Sleep Patterns at the Aisyiyah Orphanage - Nurhanifah, Dewi; Aulia, Nazi Ratul; Agim, Agim; Basri, Ahmad Hasanul; Ayu E., Chinta Kartika; Astuti, Elsi; Norkhaliza, Fitria; Fitriana, Fitriana; Maulana, Iqbal (OMNICODE Journal (Omnicompetence Community Developement Journal), 2023)
Sleep is basic needs for every human being and it has an important role in children's development. Sleep not only has an impact on physical and emotional development, but is also closely related to cognitive function, learning and attention (Liu et al., 2005). A good and regular sleep pattern can have a good effect on health (Guyton and Hall, 2012). Health education with the title "HEALTHY SLEEPING PATTERNS" aims to provide knowledge and insight to the children of the Aisyiyah orphanage about healthy sleep patterns as well as providing knowledge to the children of the Aisyiyah orphanage about sleep pattern disorders. This research was conducted at the Aisyiyah Sentosa Orphanage, Banjarmasin, targeting junior high school children who were residents of the orphanage. The method used in this research is the lecture method, discussion followed by questions and answers. The media used in this research were presentation slides in the form of power point, video leaflets, LCD, laptop and sound system. This research was carried out in several activity stages, namely the opening stage, implementation stage, evaluation stage and closing stage. The results of health education activities were successful and progressed according to the implementation stage. The success of the event can be seen from the post-test results which were all 100% correct.